The book of landings - McMorris, Mark (Wesleyan poetry., 2016)
Brings together the second and third parts of Mark McMorris's "Auditions for Utopia" trilogy. Marks two stages in the evolution of the poet's conception of space, with poetry following a trajectory of diaspora, or exile, instigated by conquest, colonialism, wars, and political defeat, which is to say the search for Utopia.